Hubungan Antara Personaliti Big Five Dengan Kepuasan Kerja Dalam Kalangan Pekerja Sokongan di UTM, Kampus Johor (Sains Humanika, 2018)
This study aims to identify the relationship between Big Five Personality and job satisfaction in UTM, Johor campus. Respondents of the study consisted of 272 support staffs. Personality Big Five was measured by using the NEO Five Factor Inventory (McCrae, 2004). Meanwhile, job satisfaction was measured by using the Minnesota Satisfaction Questionnaire (MSQ) (Weiss et al, 1967). The findings of the pilot study showed that Alpha Cronbach for Big Five Personality is between .75 to .88 and .84 to .85 for job satisfaction. Descriptive statistical analysis consists of frequency and percentage and inferential statistics of Pearson Correlation coefficients were used to test the hypothesis of the study at a significant level of .05. The findings showed that the most dominant dimension based on Big Five Personality for support staffs in UTM, Johor campus is agreeableness, whereas the level of job satisfaction is low. The results also showed that there is a significant relationship between conscientiousness and job satisfaction (r = 0.24, p
Keywords: Big Five Personality; job satisfaction